Metais pesados em sedimentos superficiais e material particulado em suspensão na Bacia Superior do Rio Itapicuru-Mirim, Jacobina, Bahia, Brasil - Santos, Marcus Vinicius Silva (2015)
Heavy metals or metallic elements have density above 5g/cm2 and atomic number greater than twenty, and several of them can be reasons for concern. The presence of metals in the environment may be related to natural or human factors, such as industrial activity, mining, smelting, agriculture or dump wastewater. Typically, the metals present adsorbed to sediment or particulate material, preferably fine-grained, and its availability is determined by physicochemical aspects, complexation with organic matter and association with other metals. The Jacobina city is known historically for gold reserves, which since the seventeenth century has caused changes in the landscape. The Itapicuru-Mirim, a tributary of Itapicuru, crosses the urban area of Jacobina receiving domestic and industrial effluents without treatment. The objective of this study was to determine the concentrations of heavy metals As, Al, Ba, Cd, Cr, Cu, Fe, Hg, Mn, Ni, Pb and Zn in the upper basin of Itapicuru-Mirim River in surface sediments and particulate matter suspension, as well as geoaccumulation index. Were determined five sampling points, which occur on a quarterly basis, from November 2013 to November 2014. After collecting the sediment carried by drying, sieving, particle size analysis by laser diffraction, analysis of the total organic matter by the method of ignition, pseudototal digestion for As and Hg elements, the total digestion and pseudototal for the other elements. Water samples were collected with plastic bottles previously washed and packed in coolers for transport to the laboratory. Filtration was carried out and determination of the particulate mass in triplicate. The metal determination was performed by ICP-AES for As, Hg mercury analyzer for ICP-OES and for other metals. For risk assessment biota was used as reference for sediment TEL guide values and PEL determined by the Canadian Council of Ministers of the Environmental. The results revealed that the superficial sediment elements Cu, Hg and Zn were above TEL and Cr, Ni and Pb were above the PEL. The Igeo pointed pollution level 3 to Pb at the closest point of the open pit, level 2 to Cr, and level 1 to Hg and Zn. The particulate matter most metals showed the highest concentrations in samples taken in the dry season, however, was in the rainy season there was greater flow of metals due to the increase of the concentration of particulate matter in the water.